The impact of national and international guidelines on newborn care in the nurseries of Piedmont and Aosta Valley, Italy - Fabris Claudio; Martano Claudio; Zaffaroni Mauro; Guarino Roberta; Guala Andrea; Pastore Guido; Bona Gianni (BMC, 2005)
Abstract Background Care procedures for preventing neonatal diseases are carried out according to nurseries' traditions and may be not consistent with the evidence based medicine issues. Methods A multi-centric survey was conducted in 2 Regions located in NW Italy (Piedmont and Aosta Valley) in order to collect information on some healthy newborn care procedures. During 2001, a questionnaire was sent to the chief pediatrician in charge to the all 33 nurseries of the region asking the methods used during 2000 as prevention of ophthalmia neonatorum, early and late hemorrhagic disease of newborn, umbilical cord care and recommendations of vitamin D administration. Thereafter, during 2004 the same questionnaire was sent to the 34 chief pediatrician of nurseries to evaluate if the procedures were changed during 2003 according to guidelines. The nurseries care for 32,516 newborns in 2000 and 37,414 in 2003. Results Aminoglycoside eyes drops as prevention of ophthalmia neonatorum were the first choice in both periods (23 out 33 nurseries in 2000 and 24 out 34 in 2003 p > 0.05; the corresponding figures for newborns were18,984 out 32,516 newborns vs. 28,180 out of 37,414 p < 0.05). The umbilical cord care was carried out with alcohol in 12/33 centers (13,248 newborns) and dry gauze in 3/33 centers (2,130 newborns) in 2000, the corresponding figures in 2003 were 6/34 centers (p > 0.05), (6,380 newborns, p < 0.05) and 12/34 centers (p < 0.05), (18,123 newborns, p < 0.05). The percentage of newborns receiving of i.m. vitamin K. at birth increased during the study period (15,923/32,104 in 2000 vs. 19,684/37,414 in 2003, p < 0.01), but not the number of nurseries (16 in 2000 and 17 in 2003 p > 0.05). The numbers of parents of newborns who receive the recommendations of oral vitamin K during the first months life decreased from 2000 (25,516/30,606) to 2003 (29,808/37,414, p < 0.01) as well as for Vitamin D recommendation (14,582/30,616 in 2000 vs. 11,051/37,414 in 2003, p < 0.01). Oral vitamin K during the first months of life was recommended by 25 nurseries in 2000 and 27 in 2003 (p > 0.05), the corresponding figures for Vitamin D were 15 and 14 (p > 0.05). Conclusion In the present study a large variability of procedures among the nurseries was observed. During the study periods, guidelines and evidence based medicine issues have only partially modified the neonatal care procedures In Piedmont and Aosta Valley nurseries. These observations suggest to implement local forum/consensus conference to standardized procedures as much as possible.